CMR quantification of myocardial scar provides additive prognostic information in nonischemic cardiomyopathy - Neilan, Tomas G; Coelho-Filho, Otavio R; Danik, Stephan B; Shah, Ravi V; Dodson, John A; Verdini, Daniel J; Tokuda, Michifumi; Daly, Caroline A; Tedrow, Usha B; Stevenson, William G; Jerosch-Herold, Michael; Ghoshhajra, Brian B; et al. (JACC. Cardiovascular imaging, 2013)
This study sought to determine whether the extent of late gadolinium enhancement (LGE) can provide additive prognostic information in patients with a nonischemic dilated cardiomyopathy (NIDC) with an indication for implantable cardioverter-defibrillator (ICD) therapy for the primary prevention of sudden cardiac death (SCD). Data suggest that the presence of LGE is a strong discriminator of events in patients with NIDC. Limited data exist on the role of LGE quantification. The extent of LGE and clinical follow-up were assessed in 162 patients with NIDC prior to ICD insertion for primary prevention of SCD. LGE extent was quantified using both the standard deviation-based (2-SD) method and the full-width half-maximum (FWHM) method. We studied 162 patients with NIDC (65% male; mean age: 55 years; left ventricular ejection fraction [LVEF]: 26 ± 8%) and followed up for major adverse cardiac events (MACE), including cardiovascular death and appropriate ICD therapy, for a mean of 29 ± 18 months. Annual MACE rates were substantially higher in patients with LGE (24%) than in those without LGE (2%). By univariate association, the presence and the extent of LGE demonstrated the strongest associations with MACE (LGE presence, hazard ratio [HR]: 14.5 [95% confidence interval (CI): 6.1 to 32.6; p < 0.001]; LGE extent, HR: 1.15 per 1% increase in volume of LGE [95% CI: 1.12 to 1.18; p < 0.0001]). Multivariate analyses showed that LGE extent was the strongest predictor in the best overall model for MACE, and a 7-fold hazard was observed per 10% LGE extent after adjustments for patient age, sex, and LVEF (adjusted HR: 7.61; p < 0.0001). LGE quantitation by 2-SD and FWHM both demonstrated robust prognostic association, with the highest MACE rate observed in patients with LGE involving >6.1% of LV myocardium. LGE extent may provide further risk stratification in patients with NIDC with a current indication for ICD implantation for the primary prevention of SCD. Strategic guidance on ICD therapy by cardiac magnetic resonance in patients with NIDC warrants further study.